Structural integrity assessment of defected high density poly-ethylene pipe: Burst test and finite element analysis based on J-integral criterion. (November 2015) - Guidara, M.A.; Bouaziz, M.A.; Schmitt, C.; Capelle, J.; Haj Taïeb, E.; Azari, Z.; Hariri, S.
Abstract: The main objective of this study was to analyze the integrity of a defective high density poly-ethylene (HDPE) pipe by computing the J-integral. To this end, an experimental test was performed to measure the toughness and to determine the mechanical behavior of the HDPE. Many burst tests were achieved on longitudinally notched pipe specimens subjected to internal pressure. The defect was machined by a disc cutter with 0.5 mm thickness. So the notch geometry was given by the disc cutter penetration in the pipe wall. Numerical simulations based on the computation of the J-integral were used to analyze the fracture behavior of these structures (notched pipe and pre-cracked pipe). The numerical results were discussed and compared with the experimental tests. Using the critical value of J-integral, the numerical simulations allowed determining the crack initiation pressure and the opening stress in the vicinity of the defect root. Numerical results show that there is a gap between the crack initiation pressures of pre-cracked pipe and those of the notched pipe. This gap increases when the defect is deeper than half of the wall thickness. These pressures decrease parabolically with the defect depth. Highlights: J-R curves and toughness J Ic of HDPE PE100 have been obtained experimentally. Burst tests were achieved on longitudinally notched PE100 pipes. 3D-FEM model based on J-integral criterion was used to analyze the defect severity. Both longitudinal notch and crack were numerically studied and compared. The numerical results show a good agreement with the experimental burst pressures.